The Implementation of Character Education in Teaching English For Young Learners - Yunita Adriyanti, Kadek (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
Character education is one of the aspects of the Indonesian educational system, which is essential for the students before they face real-world society. The strengthening of Character education has been designed in the 2013 Curriculum as one of the Indonesian government's efforts to create good quality human resources. This effort can be implemented in every subject, including English as the students’ foreign language. Children as young learners is an excellent start to be empowered not only through the knowledge of the language itself but also through inserting character values in the process of language learning. This study aims at sharing some theoretical concepts of implementing character education for young learners in the EFL class. By then, the teachers are expected to help young learners in building their positive characters.